ANALISIS PENAWARAN TENAGA KERJA WANITA MIGRAN KABUPATEN SUMBAWA - Permata Cita, Fitriah; Mujiburrahmat (Jurnal TAMBORA, 2020)
This study is entitled: "Analysis of the Migrant Women Migrant Workers' Offer". An increase in population from year to year has several logical consequences including an increase in the number of young people and an increase in the workforce. Data from the Central Statistics Agency of Sumbawa Regency shows that from 2014 to 2017 there were an increase in the population of 427,119 people, 431,924 people, 436,599 people and 441,102 people spread in 24 sub-districts. The livelihoods of most of the population (around 52.72%) make a living from the agricultural sector (BPS Sumbawa Regency 2017). The geographical condition of the Sumbawa Regency, where fertility is uneven and rainfall is also insufficient to develop normal agriculture, difficult employment opportunities, inadequate education, minimal skills, lack of venture capital, forces residents (especially women) to choose to try looking for work to become Indonesian workers to various countries including the United Arab Emirates. The purpose of this study are: 1) What is the pattern of supply of female workers from Sumbawa Regency? 2) What factors influence the decision to leave women from Sumbawa Regency to become migrant workers abroad?This research was conducted in 4 districts out of 24 districts. Each subdistrict is taken from 2-3 villages which are the basis for migrant women workers (depending on the number of migrant workers available at the time of the survey). The four subdistricts determined as sampling locations are Sumbawa District, Plampang District, Labuan Badas District and Utan District by using descriptive methods and data collection is done by observation and interview techniques. Determination of respondents is done by purposive sampling technique. The output of this research is knowing the pattern of supply of women workers from Sumbawa Regency and the factors that influence the decision to leave women from Sumbawa Regency to migrant workers abroad, so that it can be seen how the impact of working abroad for women workers and their families and their contribution to Sumbawa Regency in general. Besides that, the output of this research is published in ISSN journals and is used as reference material for Macroeconomics courses.The TKT in this study was started by identifying how the pattern of supply of women workers from Sumbawa Regency and the factors influencing the decision to leave women from Sumbawa Regency to become migrant workers outside the interview method and distributing questionnaires. Knowing the pattern of female labor supply and the factors influencing the decision of women workers to work abroad can be input for the government what will be done to women workers who work abroad and contribute to the Regency of Sumbawa.